2014
DOI: 10.4103/1305-7456.137650
|View full text |Cite
|
Sign up to set email alerts
|

Does immediate dentin sealing influence the polymerization of impression materials?

Abstract: Objectives:The objective of the following study is to evaluate the interaction between the resin materials used in immediate dentin sealing (IDS) techniques and impression materials with two different techniques to eliminate the oxygen-inhibition layer.Materials and Methods:The occlusal dentin surface of 35 human molars was exposed. The teeth were used in two Groups: Group 1 – Impression with Express XT; Group 2 – Impression with Impregum. Groups 1 and 2 were divided into 14 subgroups: Groups 1a and 2a – Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…veneers led to the proposal for posterior "occlusal veneers", which are extra-coronal restorations requiring a simpler and more intuitive preparation driven by interocclusal clearance and anatomical consideration. 10 Development of stronger materials such as lithium disilicate ceramics, hybrid ceramics and the CAD/CAM technology, [11][12][13][14][15] together with the innovative adhesive bonding protocols such as immediate dentin sealing, [16][17][18][19][20] have encouraged the introduction of bonded occlusal veneers as a conservative alternative to traditional onlays and complete coverage crowns for the treatment of severe erosion. 10,15 Federlin et al 21 and Manhart et al, 22 advocated the choice of ceramics as an enamel replacement and relied mainly on their strength and thickness, together with the effective bonding to the underlying prepared tooth structure.…”
Section: Introductionmentioning
confidence: 99%
“…veneers led to the proposal for posterior "occlusal veneers", which are extra-coronal restorations requiring a simpler and more intuitive preparation driven by interocclusal clearance and anatomical consideration. 10 Development of stronger materials such as lithium disilicate ceramics, hybrid ceramics and the CAD/CAM technology, [11][12][13][14][15] together with the innovative adhesive bonding protocols such as immediate dentin sealing, [16][17][18][19][20] have encouraged the introduction of bonded occlusal veneers as a conservative alternative to traditional onlays and complete coverage crowns for the treatment of severe erosion. 10,15 Federlin et al 21 and Manhart et al, 22 advocated the choice of ceramics as an enamel replacement and relied mainly on their strength and thickness, together with the effective bonding to the underlying prepared tooth structure.…”
Section: Introductionmentioning
confidence: 99%
“…This might affect the adhesive properties of the adhesives and resins. For this reason, a different approach that foresees the sealing of the tubules immediately after the preparation should provide positive benefits, as already indicated in the literature [17][18][19]22].…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have shown that the use of the IDS techniques can preserve the freshly cut dentinal tubules. In the same way, however, it was hypothesized that the same impression material can interact negatively on the adhesive layer applied before the impression, as recommended in the IDS protocol [19,22,23]. In a recent study in 2019, Sinjari et al [23] demonstrated how an adequate surface cleaning protocol can reset the interactions with the impression material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of a singlevisit treatment, the use of temporary sealing materials are mandatory. In addition, the unpolymerized airinhibited layer limited the polymerization reaction of impression materials 26) . However, intraoral digital impression of single-visit treatment does not contact with the resin coating layer.…”
Section: Discussionmentioning
confidence: 99%